There are two ways to do this
Method 1:
Find (f-g)(x) first
(f-g)(x) = f(x) - g(x)
(f-g)(x) = (5x^2+3) - (-2x+4)
(f-g)(x) = 5x^2+3+2x-4
(f-g)(x) = 5x^2+2x-1
Then plug in x = -3
(f-g)(-3) = 5(-3)^2+2(-3)-1
(f-g)(-3) = 5(9)+2(-3)-1
(f-g)(-3) = 45-6-1
(f-g)(-3) = 39-1
(f-g)(-3) = 38
-----------------------------------------
Method 2:
Find f(-3)
f(x) = 5x^2+3
f(-3) = 5(-3)^2+3
f(-3) = 5(9)+3
f(-3) = 45+3
f(-3) = 48
Find g(-3)
g(x) = -2x+4
g(-3) = -2(-3)+4
g(-3) = 6+4
g(-3) = 10
Subtract the two results
(f-g)(-3) = f(-3) - g(-3)
(f-g)(-3) = 48 - 10
(f-g)(-3) = 38
-----------------------------------------
Whichever method you pick, the answer is: 38
Set up a proportion. 6/10 = 9/x. cross multiply so x times 6 = 6x. And 10 times 9 = 90. so 6x=90. Then 90 and 6x divided by 6. which gets you x=15. The 9 ft tall elephant will cast a 15 ft shadow.
Answer: 15 miles
Step-by-step explanation:
The equation is 5.25+1.25x=24 where x is each additional mile so to solve for x it would be 1.25x=18.75 and divide both sides to solve for x
2x=y where 2 is dollars per tomatoe, x is amount of pounds of tomatoes, and y is amount of money spent in total. say you got 3 pounds of tomatoes; the equation would be 2(3)=y. y=6. Hope I helped!